(untitled) (International Journal of Innovative Technologies in Economy, 2025)
This study explores the role of Artificial Intelligence (AI) in enhancing the competitiveness of Algerian companies through its integration into digital marketing strategies. The research focuses on the case of Venus Company, which has adopted several AI-based tools such as data analytics, predictive modeling, and personalized advertising systems. Using a descriptive-analytical methodology supported by quantitative data, the study reveals that AI technologies significantly improve marketing performance indicators, including customer engagement, cost efficiency, and market adaptability. The findings demonstrate that AI enhances decision-making precision, facilitates customer relationship management, and strengthens the company’s competitive positioning in an increasingly digitalized market. The research concludes with recommendations for Algerian enterprises to invest strategically in AI-driven marketing innovations and develop internal competencies capable of leveraging these technologies for sustainable competitive advantage.